TPACK-Approach with SAMR Model in Social Studies Learning: A Literature Review - Piki Setri Pernantah (UIN Fatmawati Sukarno Bengkulu, 2024)
The transformation of social studies learning in the 21st century era is indeed necessary to continue to be carried out, one of which is how to integrate technology into social studies learning in schools. This is because integrated social studies learning by accompanying the effective use of technology can add an important dimension to student learning. Efforts to integrate technology into social studies learning can be done through the TPACK approach and the SAMR model. Both models offer frameworks that can assist social studies teachers in adopting technology effectively in social studies learning in the classroom. The method used in this study is a qualitative approach with a literature method involving the analysis and synthesis of relevant literature to explain or understand this study. The implications of the SMAR model TPACK approach allow social studies teachers to increase student involvement and understanding of social studies learning materials. This certainly creates a richer and more meaningful learning experience, as well as helping students develop critical thinking skills that are relevant to today's 21st century competency demands.